Identifying the poor in Indonesia: poverty measures and data sources - Gerke, Solvay (Universiti Kebangsaan Malaysia, 2002)
The rise of poverty in Indonesia since the monetary crisis of 1997 has been of major concern to the Indonesian government, international agencies and scholars. In this paper the writer aim to identify the various dimensions of poverty and to discuss the problem of identifying the poor. The paper provides information on the main data sources in Indonesia and outlines how poverty is measured on the national and local level. In conclusion different data sets and poverty measures are compared and evaluated as to their reliability and usefulness.